Oral Biopsy: Evaluating Awareness and Knowledge Among Dental Students at University of Baghdad: Oral Biopsy: Evaluating Awareness and Knowledge Among Dental Students - maryam hameed alwan; Dania Mahdi A. Alhussain; Tiba Haider Muneer (YARSI Dental Scientific Meeting - e Journal, 2025)
Introduction Oral biopsy is a fundamental diagnostic procedure in dentistry, essential for the early detection of oral cancer and other pathologies. While theoretical knowledge is a core component of dental education, the translation of this knowledge into clinical confidence and practical ability is critical for patient care. Objective: : evaluate the awareness, knowledge, and self-perceived ability to perform oral biopsies Material and Methods: A cross-sectional study was conducted among dental students. Participants (n=110) comprising 14 multiple-choice questions assessing key variables: knowledge of biopsy principles, techniques, lesion identification, specimen preservation, and ability to perform the procedure Results: While theoretical awareness was high (98% knew what a biopsy is), a significant gap existed with practical application. Only 16% of students felt confident performing a biopsy independently. The primary barriers were reliance on theoretical knowledge only (47%) and a lack of clinical training (37%). A statistically significant association was found between gender and the perceived ability to perform a biopsy (p=0.002). However, no significant correlation was found between academic stage (4th vs. 5th year) and practical ability (p=0.2). Conclusion: Dental students have a strong theoretical foundation in oral biopsy but report a significant deficit in practical, hands-on training and self-confidence. The findings highlight a critical need to reform the curriculum to include more clinical and simulation-based training to bridge this theory-practice gap and better prepare future dentists for this essential diagnostic responsibility